Association between Frequency of Breakfast Consumption and Academic Performance in Healthy Korean Adolescents. - Wi-Young So (Tehran University of Medical Sciences, 2013)
The purpose of this study was to examine whether the frequency of breakfast consumption was related to academic performance in healthy Korean adolescents.We analyzed data from the seventh Korea Youth Risk Behavior Web-based Survey conducted in 2011, in which 75,643 adolescents from school grades 7-12 participated. We assessed the association between the frequency of breakfast consumption (per week) and academic performance using multivariate logistic regression analysis after adjusting for covariates such as age, body mass index, frequency of smoking, frequency of drinking, parents' education level, family economic status, frequency of vigorous physical activity (PA), frequency of moderate PA, frequency of muscular strength exercises, and level of mental stress.For male adolescents, the odds ratios (ORs) for achieving average or higher academic performance according to the breakfast frequency per week were once per week, 1.004 (P=0.945); twice per week, 0.915 (P=0.153); 3 days per week, 0.928 (P=0.237); 4 days per week, 1.087 (P=0.176); 5 days per week, 1.258 (P